2022
DOI: 10.1093/nargab/lqac055
|View full text |Cite
|
Sign up to set email alerts
|

Ψ-Footprinting approach for the identification of protein synthesis inhibitor producers

Abstract: Today, one of the biggest challenges in antibiotic research is a targeted prioritization of natural compound producer strains and an efficient dereplication process to avoid undesired rediscovery of already known substances. Thereby, genome sequence-driven mining strategies are often superior to wet-lab experiments because they are generally faster and less resource-intensive. In the current study, we report on the development of a novel in silico screening approach to evaluate the genetic potential of bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Assays were carried out and evaluated as reported before. 51 Based on previous studies, iv TT fluorescence values of 0–20% indicate strong inhibition of the assay, 0–40% are considered to represent specific inhibition, whereas values above 40% do not indicate inhibition of the iv TT assay. In iv TT assays with pristinamycin derivatives, it was found that pristinamycin II resulted in strong inhibition of the iv TT assay, whereas neither pristinamycin I ( 1 ) nor the halogenated pristinamycin I derivatives 3 and 4 led to an inhibition (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assays were carried out and evaluated as reported before. 51 Based on previous studies, iv TT fluorescence values of 0–20% indicate strong inhibition of the assay, 0–40% are considered to represent specific inhibition, whereas values above 40% do not indicate inhibition of the iv TT assay. In iv TT assays with pristinamycin derivatives, it was found that pristinamycin II resulted in strong inhibition of the iv TT assay, whereas neither pristinamycin I ( 1 ) nor the halogenated pristinamycin I derivatives 3 and 4 led to an inhibition (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…13 In vitro transcription and translation (ivTT) assay with pristinamycin I derivatives Semi-purified HPLC fractions of 1, 3, and 4 were tested in ivTT assays. Assays were carried out as reported before 51 and were conducted in triplicates. Each assay had an end concentration of approximately 0.5 mg mL À1 of 1, 3, 4, or PI standard (Sanofi-Aventis) with or without the addition of 0.5 mg mL À1 pristinamycin II standard (Sanofi-Aventis), respectively.…”
Section: Cytotoxicity Testsmentioning
confidence: 99%
“…The strains DSM 40484 T , DSM 40713 T , DSM 40907 T , DSM 40971 T , and DSM 40976 T were cultivated by inoculation from a GYM plate in 50 mL medium R5 (103 g L −1 sucrose, 10 g L −1 glucose, 0.25 g L −1 K 2 SO 4 , 10.12 g L −1 MgCl 2 x 6 H 2 O, 0.1 g L −1 casamino acids, 5 g L −1 yeast extract, 5.73 g L −1 TES (pH 7.2), 2.94 g L −1 CaCl 2 x 2H 2 O, 0.05 g L −1 KH 2 PO 4 , 3 g L −1 L-proline, and 2 mL trace element solution, according to the work of Handel et al (2022) ; pH 7.4) at 28°C in 250 mL Erlenmeyer flasks on an orbital shaker (180 rpm). After 2 days of cultivation, 5 mL of the preculture was used to inoculate 250 mL Erlenmeyer flasks with 50 mL of production media R5 or NL 800 (5 g L −1 glucose, 10 g L −1 glycerol, 10 g L −1 soluble starch, 58 g L −1 oatmeal, 2 g L −1 yeast extract, 1 g L −1 NaCl, and 1 g L −1 CaCO 3 ; pH 7.2) as production cultures, which were incubated for 3 days at 28°C on an orbital shaker at 180 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…DSM 40976 T by conjugation, as described by Kieser et al (2000) , resulting in the strain DSM 40976 T pGM1190/ papR2-tipA p. Apramycin (50 μg/mL) was used for selection when appropriate. To test for the effect of papR2 expression on secondary metabolite production, the strain DSM 40976 T pGM1190/ papR2-tipA p and the WT strain were each cultivated in OM medium (20 g L −1 oat meal, 5 mL trace element solution, pH 7.3; according to Handel et al (2022) ) at 28°C; 20 mL of culture was harvested after 72 h of cultivation. For extraction of organic compounds, cultures were treated as described above.…”
Section: Methodsmentioning
confidence: 99%
“…A specialized platform for the search for such resistance determinants (Antibiotic-Resistant Target Seeker (ARTS)) [ 124 , 125 ] and a database with pre-computed ARTS results for >70,000 genomes were developed by Prof. Ziemert’s group [ 126 ]. This approach, called Ψ-footprinting, was also recently adapted to the search for protein synthesis inhibitors (PSI = Ψ) [ 127 ].…”
Section: Molecular Biologymentioning
confidence: 99%